2021
DOI: 10.1002/star.202100202
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and Acidic Hydrolysis of Cull Potatoes for Production of Fermentable Sugars

Abstract: Cull potato is an under-utilized biomass being produced in different states of India. Using cull potatoes as a substrate for bioethanol production can overcome the post-harvest losses as well as making the process economical. In the present study, comparative hydrolysis of cull potatoes is carried out using enzymes and hydrochloric acid to study the effect of variables on saccharification efficiency. For enzymatic hydrolysis, samples are liquefied using crude enzyme from Bacillus sp. and then saccharification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…In a recent study by Bansal et al (2022), it was found that the efficiency of enzymatic hydrolysis does not significantly impact the generation of fermentable sugars compared to acidic hydrolysis. Enzymatic hydrolysis is commonly utilized as an initial step in certain processes to minimize chemical usage and energy consumption.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study by Bansal et al (2022), it was found that the efficiency of enzymatic hydrolysis does not significantly impact the generation of fermentable sugars compared to acidic hydrolysis. Enzymatic hydrolysis is commonly utilized as an initial step in certain processes to minimize chemical usage and energy consumption.…”
Section: Discussionmentioning
confidence: 98%